Dynamic interpersonal therapy in an NHS tertiary level specialist psychotherapy service. Issue 3 (2nd July 2016) - Douglas, Angela; Ablett-Tate, Nicky; Chadd, Nicola
Abstract : We describe the introduction of dynamic interpersonal psychotherapy (DIT) into an National Health Service (NHS) tertiary psychoanalytic specialist psychotherapy service. Training in DIT began as our contribution to Improving Access to Psychological Therapies and primary care services, supporting the training and supervision of their DIT practitioners. We then discovered DIT could be a valuable treatment within our own tertiary NHS service for patients with complex presentations. Currently fighting for survival, like many NHS psychoanalytic psychotherapy services nationally, we have adopted a manual-guided, psychoanalytically based therapy to broaden our tertiary clinical psychoanalytic service and accommodate trends in mental health service provision, whilst protecting the quality and integrity of our psychotherapy. DIT helped us continue providing relevant and beneficial psychoanalytic and psychodynamic services to individual patients despite limitations of the financially challenged NHS, NICE guidelines and Payment by Results. We outline the progress and outcomes for patients with complex mental health presentations, include individual case discussion and our experience of using the DIT approach within a traditionally longer term psychoanalytic psychotherapy service.